From Denture to the Final Implant-Supported Prosthesis Using a Full-Digital Protocol: A Dental Technique - Francisco Fernando Todescan; Marcos Masayuki Hayashi; Luiz Roberto Giugni; Marco Antonio Bottino; João Paulo Mendes Tribst (MDPI AG, 2021)
Proper maxillomandibular relationship registration can be clinically challenging during a digital workflow in full-arch rehabilitations. This dental technique requires the manufacturing and use of a hybrid surgical guide custom scanning device, indicated to be used during implant placement surgery, in addition to being used to simultaneously register the maxillomandibular relationship and transfer the implants' 3D positioning, ensuring a fully digital workflow in full-arch implant-supported prosthesis rehabilitation. The sequence of steps presented here will allow dentists and dental technicians to conduct rehabilitations from denture to the final implant-supported prosthesis using a full-digital protocol, using a minimal quantity of intraoral devices and digital tools.